MARKETING COMMUNICATION STRATEGY: Case Study of Product Marketing Communication Strategy on Riseloka.com website - Nugraha, Harry; Santo Hegiarto, Aldy (Universitas Islam Lamongan, 2024)
This research aims to find out the marketing communication strategy at Riseloka.com in increasing product sales. This research uses a qualitative descriptive method, which is research that tries to describe or describe the object under study based on the facts in the field. The data presented uses secondary data primary data through structured interviews, observation, and documentation related to this research, then the data analysis technique used in this research technique is qualitative data analysis. The results of this study indicate that the marketing communication strategies implemented by Riseloka.com are advertising and direct marketing. Advertising uses the marketplace and through social media. While direct marketing is done using social media to individuals and companies/agencies. Of the two strategies carried out, advertising through social media (online) is more routinely carried out because it is considered more effective and efficient. Meanwhile, direct marketing through the marketplace is carried out regularly at least 3 times a year and can even be more frequent in accordance with technological advances.